Competencies in ICT of teachers and their relation to the use of the technological resources - Suárez Rodríguez, Jesús M.; Almerich, Gonzalo; Gargallo López Bernardo; Aliaga, Francisco M. (Education Policy Analysis Archives, 2010)
Over the past decade the Information and Communication Technologies (ICT) have represented a transformation of education policies that have entailed important investments. However, the teacher, as a key element in the integration process of ICT, still does not feel trusted this process. One of the most outstanding causes of this deficit confidence is the lack of teaching staff competence in the ICT. Therefore, the aim of this paper is a study of the teachers’ competence on ICT and their relation to the use being made of these technologies, both professional-personal and with their students. For it a survey design has been used. The target population constitutes the teaching staff of centers of primary and secondary education of the Comunidad Valenciana. Information was collected through questionnaires. Starting from the technological and pedagogic competences in TIC, we have been obtained teachers’ consistent competencies profile with four increasing levels: without knowledge, entrance, adoption and innovation. Likewise, we has been a narrow relationship among this profile and the use that the teachers carries out, more closely connected with the personal-professional who with the use with the students. Findings contribute keys to guide the professional development and teacher initial education programs.